O desenvolvimento urbano do município mato-grossense de Várzea Grande no período de 1964 a 1988 - Santos, Wallison Ulisses Silva dos (2016)
This research aimed to understand the process of economic development of the municipality of Várzea Grande, in Mato Grosso, supported in economic history during the period from 1964 to 1988. The aim was to understand the relationship between the economic growth of this period in the city and social development. In order to achieve the proposed objectives were carried out research on major economic theories, the development in the design of Celso Furtado and theories about urbanization as a way of such restrictions analysis of their secondary indicators of the municipality, as well as existing works on the local. newspaper materials were raised and analyzed on Várzea Grande and interviews with locals who lived in the city in the period of this research. The results pointed to a process of economic growth without systemic improvements in social conditions in this sense it can be said that there has been economic growth, but hardly say that there was development. Progress in literature, as in the press appears to be a capital accumulation process for the benefit of a minority, this ideology was apparently one of process bases that generated capital accumulation in the city, but it did not return in the same proportion development.